![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) ( 1456 + 323 ) - 1456
= 1456 + 323 - 1456
= ( 1456 - 1456 ) + 323 = 323
b ) ( - 1999 ) - ( - 234 - 1999)
= - 1999 + 234 + 1999
= ( - 1999 + 1999 ) + 234 = 0 + 234 = 234
![](https://rs.olm.vn/images/avt/0.png?1311)
a.(1456+23)-1456
=1456+23-1456
=(1456-1456)+23
=23
b.(-1999)-(-234-1999)
=-1999-(-234)+1999
=(-1999+1999)-(-234)
=-(-234)
=234
c.(116+124)+(215-116-124)
=116+124+215-116-124
=(166-166)+(124-124)+215
=215
d.(435-167-89)-(435-89)
=435-167-89-435+89
=(435-435)-(89-89)-167
=-167
k for more
#hungB
a) = 1456 + 23 - 1456
= ( 1456 - 1456 ) + 23
= 0 + 23
= 23
b) = ( -1999 ) + 234 + 1999
= ( -1999 + 1999 ) + 234
= 0 + 234
= 234
c) = 116 + 124 + 215 - 116 - 124
= ( 116 - 116 ) + ( 124 - 124 ) + 215
= 0 + 0 + 215
= 215
d) = 435 - 167 - 89 - 435 + 89
= ( 435 - 435 ) + ( -89 + 89 ) - 167
= 0 + 0 - 167
= -167
![](https://rs.olm.vn/images/avt/0.png?1311)
=2666666000
Có công thức như sau
1x2+2x3+3x4+...+nx(n+1)=nx(n+1)x(n+2):3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = ( 1999/2011 - 2011/1999 ) - ( -12/1999 - 12/2011 )
=1999/2011-2011/1999+12/1999+12/2011
=(1999/2011+12/2011)-(2011/1999-12/1999)
=1-1
=0
Vậy A=0
B = 2/5 + [ 3/11 + (-2)/5 ]
=[2/5+(-2/5)]+3/11
=0+3/11
=3/11
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1999}{2011}-\frac{2011}{1999}-\left(\frac{-12}{1999}-\frac{12}{2011}\right)\)
\(=\frac{1999}{2011}-\frac{2011}{1999}+\frac{12}{1999}+\frac{12}{2011}\)
\(=\left(\frac{1999}{2011}+\frac{12}{2011}\right)-\frac{2011}{1999}+\frac{12}{1999}\)
\(=1-\left(\frac{2011}{1999}-\frac{12}{1999}\right)\)
\(=1-1\)
\(=0\)
NHÉ !!!!!!!
Ta có : \(\frac{1999}{2011}-\frac{2011}{1999}-\left(\frac{-12}{1999}-\frac{12}{2011}\right)\)
=\(\frac{1999}{2011}-\frac{2011}{1999}+\frac{12}{1999}+\frac{12}{2011}\)
=\(\left(\frac{1999}{2011}+\frac{12}{2011}\right)+\left(\frac{12}{1999}-\frac{2011}{1999}\right)\)
=1-1
=0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{1999}{2011}-\frac{2011}{1999}\right)-\left(\frac{-12}{1999}-\frac{12}{2011}\right)\)
\(=\frac{1999}{2011}-\frac{2011}{1999}+\frac{12}{1999}+\frac{12}{2011}\)
\(=\left(\frac{1999}{2011}+\frac{12}{2011}\right)+\left(-\frac{2011}{1999}+\frac{12}{1999}\right)\)
\(=\frac{2011}{2011}+\frac{-1999}{1999}=1+\left(-1\right)=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có
19991999.1998-19981998.1999
=1999. 10001 .1998-1998.10001.1999
=0